2020
DOI: 10.1111/nan.12661
|View full text |Cite
|
Sign up to set email alerts
|

Signs of early cellular dysfunction in multiple system atrophy

Abstract: Signs of early cellular dysfunction in multiple system atrophy Aims: Multiple system atrophy (MSA) is a fatal neurodegenerative disease that belongs to the family of asynucleinopathies. At post mortem examination, intracellular inclusions of misfolded a-synuclein are found in neurons and oligodendrocytes and are considered to play a significant role in the pathogenesis. However, the early steps of the disease process are unknown and difficult to study in tissue derived from end-stage disease. Methods: Induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 59 publications
0
12
1
Order By: Relevance
“…Although we did not detect any overt signs of mature fibril-like inclusions in isolated nuclei, neuronal and oligodendrocytic intranuclear inclusions of β-sheet rich aSyn filaments are a pathological feature of MSA, alongside aSyn cytoplasmic aggregates (16). In MSA, elevated pS129 aSyn Nuc is considered as an early pathological event, present in preclinical cases (67) and patient derived neural progenitor cells (68). This initial increase in intranuclear diffuse or punctate staining, similar to what was observed in the present study, is assumed to precede the formation of thioflavin positive aggregates (67).…”
Section: Disease-dependent Modification Of Asyn Nuccontrasting
confidence: 49%
“…Although we did not detect any overt signs of mature fibril-like inclusions in isolated nuclei, neuronal and oligodendrocytic intranuclear inclusions of β-sheet rich aSyn filaments are a pathological feature of MSA, alongside aSyn cytoplasmic aggregates (16). In MSA, elevated pS129 aSyn Nuc is considered as an early pathological event, present in preclinical cases (67) and patient derived neural progenitor cells (68). This initial increase in intranuclear diffuse or punctate staining, similar to what was observed in the present study, is assumed to precede the formation of thioflavin positive aggregates (67).…”
Section: Disease-dependent Modification Of Asyn Nuccontrasting
confidence: 49%
“…Zhou et al (2016) found that increased serum levels of homocysteine and reduced serum levels of high-density lipoprotein cholesterol were potential prognostic biomarkers associated with the disease severity of MSA patients. In another study, Herrera-Vaquero et al (2020) observed increased levels of tubulation in the mitochondria of neural progenitor cells from MSA patients and that ROS could promote the translocation of α-synuclein into nucleus, thus suggesting that oxidative stress plays a key role in MSA at early onset. In addition, Glat et al (2020) found that oxidative stress-related genes were up-regulated in a mouse model of MSA and that an injection of mitochondrial neurotoxin could improve motor function.…”
Section: Discussionmentioning
confidence: 98%
“…Although we did not detect overt signs of mature fibril inclusions, neuronal and oligodendrocytic intranuclear inclusions of aSyn filaments are a pathological feature of MSA, alongside aSyn cytoplasmic aggregates [ 34 ]. As part of the MSA disease process elevated pS129 aSyn Nuc is considered as an early event and is assumed to precede the formation of mature aggregates [ 25 , 70 ]. In any case, the occurrence of neuronal nuclear inclusions in the brain stem nuclei of MSA cases correlates with surviving neuron numbers, suggestive of a protective role for mature inclusions [ 50 ], which is in line with cellular toxicity being largely independent of overt aSyn aggregates in cell models [ 68 ] and that instead, at least within the nucleus, toxicity may be driven by intermediate aSyn oligomers [ 67 ].…”
Section: Discussionmentioning
confidence: 99%